Distinct Subfamilies of Odorant Binding Proteins in Locust (Orthoptera, Acrididae): Molecular Evolution, Structural Variation, and Sensilla-Specific Expression - Jiang, Xingcong; Krieger, Jürgen; Breer, Heinz; Pregitzer, Pablo (Frontiers in Physiology, 2017)
Odorant binding proteins (OBPs) play an important role in insect olfaction, facilitating transportation of odorant molecules in the sensillum lymph. While most of the researches are concentrated on Lepidopteran and Dipteran species, our knowledge about Orthopteran species is still very limited. In this study, we have investigated OBPs of the desert locust Schistocerca gregaria, a representative Orthopteran species. We have identified 14 transcripts from a S. gregaria antennal transcriptome encoding SgreOBPs, and recapitulated the phylogenetic relationship of SgreOBPs together with OBPs from three other locust species. Two conserved subfamilies of classic OBPs have been identified, named I-A and II-A, exhibiting both common and subfamily-specific amino acid motifs. Distinct evolutionary features were observed for subfamily I-A and II-A OBPs. Surface topology and interior cavity were elucidated for OBP members from the two subfamilies. Antennal topographic expression revealed distinct sensilla- and cellular- specific expression patterns for SgreOBPs from subfamily I-A and II-A. These findings give first insight into the repertoire of locust OBPs with respect to their molecular and evolutionary features as well as their expression in the antenna, which may serve as an initial step to unravel specific roles of distinct OBP subfamilies in locust olfaction.